Teachers' Participation in Decision-Making, Professional Growth, Appraisal, and Behavioral Intentions in the Promotion System Reform in Chinese Universities - Peng, Wangxin; Nair, Subadrah Madhawa (Frontiers in Psychology, 2022)
The promotion system in Chinese universities has been undergoing a reform since 2017. This study employed an online survey validated by confirmatory factor analysis with 372 Chinese teachers to investigate the extent to which they were empowered by the two practices of participation in decision-making and professional growth in the reform and level of their appraisal of and behavioral intentions toward the new promotion system. Structural equation modeling was used to measure how the two empowerment practices influenced the teachers' appraisal of and behavioral intentions toward the new system. The findings suggest that the Chinese teachers had low participation in decision-making and medium institutional support for professional growth, relatively low nonmonetary cost-benefit appraisal and medium practicality and fairness appraisal of the new system, and relatively high behavioral intentions to increase efforts according to the new system. Besides, participation in decision-making had a significantly direct effect on practicality and nonmonetary cost-benefit appraisal. Professional growth had a significantly direct effect on practicality, fairness, and nonmonetary cost-benefit appraisal and behavioral intentions. Nonmonetary cost-benefit appraisal had a significantly direct effect on behavioral intentions. The implications are that, in promotion system reforms, the two empowerment strategies of shared decision-making and professional growth can help establish a new promotion system with high nonmonetary cost-benefits for teachers and raise teachers' behavioral intentions to develop and pursue promotion. They can also contribute to the formulation of a new promotion system that effectively evaluates individual teacher's achievements according to the characteristics of the specific university, teacher type, and discipline. This study had the limitations of using convenience sampling, collecting cross-sectional data through self-administered questionnaires, and reporting only teachers' side of the story. Therefore, it is recommended that future studies target both teachers and administrators, employ a mixed-method design, collect quantitative data through random sampling, and take a longitudinal view.